Complete Bilateral Agenesis of the Diaphragm: A Case Report and Literature Review. (February 2017) - Al-Adnani, Mudher; Marnerides, Andreas
Bilateral agenesis of the diaphragm is a very rare congenital diaphragmatic defect. Bilateral congenital diaphragmatic hernia (CDH) is much more frequently associated with other anomalies compared with unilateral CDH (70% vs 30%–40%). These include cardiovascular, respiratory (other than lung hypoplasia), gastrointestinal, renal, and genital malformations. We report a case of complete bilateral agenesis of the diaphragm associated with a horseshoe kidney and an imperforate anus. These additional malformations have not previously been reported in association with complete bilateral agenesis of the diaphragm. We also present a review of previous cases of total diaphragm agenesis published in the English language and provide some insights about pathogenesis.